KINERJA DINAS KEHUTANAN DAN PERKEBUNAN KABUPATEN DONGGALA DALAM PROSES PELAKSANAAN RENCANA KERJA TAHUN 2014 - Amin, Amin (Katalogis, 2016)
After the implementation of the act of number 25 th ofÂ 2004 on the national planning systim, The implementation of the work plan expected arrgement of stakeholder engagement both in organization and community. This process it is a guarantee inception harmonisation organization in achieving a good performance.Hence this study attempts to actualize renja 2014 to set out in budget work plan 2014 and described the impact of implentasi of the performance of the forestry office and plantation Donggala. The methodology used is descriptive qualitative.Excavation data over technique interviews, observation, and study documentation, conducted in two stages.The first stage with variable-variable used is the quality of the work plan, the KUA and PPAS, and budget plan work variable bound us and officials involved in the process of implementation variable free us. The second stage is measuring performance by the effectiveness of, the quality of services and responsibilitas as variable bound and the and staff at the office of forestry and plantation and other stakeholders as variable free.To research there are also variable moderator the local regulations the way the process budgeting until performance. The conclusion of this study is it turns out that the implementation of the work plan year 2014 on the performance of the forestry office and plantation donggala happened inconsistency of work plans and the budget work plan so it influences the effectiveness of , the quality of services and responsibilitas in public service and the technical the forestry office and plantation donggala. The cause was the low quality of documents work plan, that has not been coordination between related agencies involved in budgeting, the domination leadership of skpd and council in priority setting activities and poor participation officials skpd and the community in the process of drafting the and activities. Advice who writers proposing is required the increase in coordination and capacity building officials involved either directly or indirectly in the process of developing a budget and work plan on the skpd level need to the reduction of the domination power in the process of drafting the work plan budget.